English English - Trisa Diptami P; Budi W. Soetjipto (Faculty of Economics and Business Udayana University, 2025)
Market turbulence compels SMEs to innovate through strategic flexibility and organizational creativity to maintain a competitive advantage. In Bali, SMEs face challenges such as a lack of organizational creativity, limited understanding of knowledge management, and the pressing need for innovation in a competitive landscape. This study aims to investigate the relationship between innovation performance and factors such as knowledge management, strategic flexibility, and organizational creativity in Bali's SMEs during the COVID-19 pandemic. While dynamic capability is crucial for organizational sustainability, research connecting strategic flexibility and organizational creativity to innovation performance remains scarce. Adopting a quantitative approach, data will be collected through questionnaires distributed to 431 UKM managers. The findings suggest that SMEs that leverage performance standards, engage in effective strategic planning, and embrace diverse ideas can make significant contributions to their industry and effectively meet customer needs. Keywords: dynamic capabilities theory; knowledge management; strategic flexibility; organizational creativity; innovation performance